Autoimmune diseases as pre-existing conditions and sequelae of post COVID-19 condition in a Massachusetts community based observational study of COVID-19 patients - Susan R. Sama; Rebecca Gore; Ann Z. Bauer; Lawrence Garber; Richard Rosiello; Meagan Fair; David Kriebel (PLoS ONE, 2025)
Between 10%−26% of COVID patients develop Post COVID condition (PCC). The complex interaction between autoimmunity and SARS-CoV-2 is emerging as an important challenge and an opportunity to improve diagnosis and treatment of immune mediated chronic illnesses. In a retrospective cohort study using electronic health records from a Massachusetts group medical practice, we identified 38,327 patients with a COVID-19 diagnosis and 1,143 with a PCC diagnosis from 1/1/2020 to 6/25/2023. We investigated the hypotheses that auto-immune diseases-1) increase risk of developing PCC; 2) were more likely to develop after COVID-19; and 3) medical utilization would be higher in patients with a PCC diagnosis. We compared COVID-19 patients with and without a PCC diagnosis. We evaluated demographics, PCC symptoms, pre-infection comorbidities, autoimmune diseases pre- and post- SARS-CoV-2 infection, and medical utilization. Females were more likely to have a PCC diagnosis (63%, p = 0.012). High BMI (> 30), pre-infection chronic respiratory disease, and “any post-infection autoimmune disease” were also associated with PCC diagnosis, OR= 1.25, (95% CI: 1.11, 1.41); OR=1.64, (95% CI: 1.45, 1.86), OR=1.57, (95% CI: 1.10, 2.24), respectively. Pre-infection, psoriasis OR=1.41 (95% CI: 1.04, 1.91) and rheumatoid arthritis OR=1.64, (95% CI: 1.00, 2.69) were more likely to be observed in patients with a PCC diagnosis. Post-infection, Sjögren’s syndrome, OR=4.05 (95% CI: 1.94, 8.49) was more likely among PCC diagnosed patients and rheumatoid arthritis OR=3.18 (95% CI: 0.99, 10.46) may also be more prevalent. We observed approximately one more day of medical utilization per month among patients with a PCC diagnosis (p < 0.001). We confirm PCC diagnosis is more prevalent among women, patients with high BMI and chronic respiratory disease. Our findings support emerging evidence that pre-existing autoimmune diseases may increase risk of PCC, SARS-CoV-2 may increase the risk of new onset autoimmune disease, and medical utilization is higher among patients with PCC.